(untitled) (Revista Brasileira Multidisciplinar, 2025)
Using an exploratory research methodology, this research seeks to provide support to designers and health professionals in creating built spaces capable of contributing to cognitive health and continuous learning throughout users’ lives. To achieve this objective, the experimental concept of environmental enrichment (EA) was investigated through an integrative literature review, exploring its neuroscientific contributions in relation to the significant influence that the physical environment and its possibilities can exert on the structure of the brain, resulting in biological, psychological and social changes, especially during human aging. Although studies related to EA and brain plasticity generally consider animal models, it is clear that exposure to enriched environments can induce beneficial structural changes in the brain, resulting in improvements in cognitive capabilities, such as learning and cognitive reserve. The practical application of these concepts is configured through a diagram of design propositions, which can be incorporated into current and future architectural and urban constructions. This approach is supported by recent research with human models carried out over the last three years. Effects capable of mitigating chronic stress, anxiety and cognitive decline are constantly identified in the studies analyzed. Thus, considering the significant potential that the built environment has to influence human behavior, approaches that integrate neuroscience, architecture and learning are considered essential for the design of spaces aligned with the promotion of cognitive health throughout life.